Adrenal venous sampling with adrenocorticotropic hormone stimulation: A meta‐analysis. Issue 9 (16th June 2021) - Yang, Junfeng; Yu, Yanhong; Zhang, Zhuorui; Wu, Yuerong; He, Zhengyu
Abstract: Background: This meta‐analysis was performed to compare the effect of adrenal venous sampling with adrenocorticotropic hormone with that without adrenocorticotropic hormone in subjects with primary aldosteronism. Methods: A systematic literature search up to May 2020 was performed and 17 studies were detected with 1878 subjects who had adrenal venous sampling operations. They reported relationships between with and without adrenocorticotropic hormone stimulation during adrenal venous sampling in subjects with primary aldosteronism. We calculated the odds ratio (OR) with 95% confidence intervals (CIs), using the dichotomous method with a random‐ or fixed‐effect model. Results: Adrenal venous sampling operations with adrenocorticotropic hormone stimulation had statistically significant lower incorrect lateralisation (OR, 0.57; 95% CI, 0.43‐0.75, P < .001); lower unsuccessful cannulations in both adrenal veins (OR, 0.35; 95% CI, 0.21‐0.58, P < .001); lower unsuccessful cannulations of left adrenal vein (OR, 0.10; 95% CI, 0.06‐0.17, P < .001) and lower unsuccessful cannulations of right adrenal vein (OR, 0.25; 95% CI, 0.11‐0.54, P < .001) compared with without adrenocorticotropic hormone stimulation in subjects with primary aldosteronism. Conclusions: Adrenal venous sampling operations with adrenocorticotropic hormone stimulation had significantly lower incorrect lateralisation, unsuccessful cannulations in both adrenal veins, unsuccessful cannulations of the left adrenal vein and unsuccessful cannulations of the right adrenal vein compared with adrenal venous sampling operations without adrenocorticotropic hormone stimulation in subjects with primary aldosteronism. Larger prospective studies are recommended to confirm these findings.